An Analysis of Listening Comprehension Problems in Listening Subject Among Students in English Language Education Study Program of San Pedro University - Sene, Chamelya Vivi Crystanty (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This study examined the listening comprehension issues that first-semester English language education program students encountered. A descriptive and qualitative methodology was used to conduct this study. Six students participated in this research during the first semester. Two sections of the questionnaire were filled out on paper. The result of the questionnaire showed that in the section listening material, 83% of them occasionally find it challenging to understand the complex grammatical structures related to English vocabulary when solving listening problems. Nonetheless, the majority of them selected "sometimes" in the questionnaire's listener problems section. According to the fifth statement in the section on listeners' problems, 50% of them find it difficult to respond to questions that require more detail than a brief answer because they lack the necessary vocabulary, there are a few recommendations that can be made. First, students should practice listening to English more frequently in order to improve their listening skills. Additionally, because grammar and vocabulary are crucial, students need to dedicate more time to developing them.